Dengue and Zika virus infection patterns vary among Aedes aegypti field populations from Belo Horizonte, a Brazilian endemic city. - Raquel Soares Maia Godoy; Luiza Dos Santos Felix; Alessandra da Silva Orfanó; Bárbara Aparecida Chaves; Paula Monalisa Nogueira; Breno Dos Anjos Costa; Aline Silva Soares; Cinthia Catharina Azevedo Oliveira; Rafael Nacif-Pimenta; Breno Mello Silva; Ana Paula Duarte; Marcus Vinicius Guimarães de Lacerda; et al. (Public Library of Science (PLoS), 2021)
Dengue virus (DENV) and Zika virus (ZIKV) belong to the same viral family, the Flaviviridae. They cause recurring threats to the public health systems of tropical countries such as Brazil. The primary Brazilian vector of both viruses is the mosquito Aedes aegypti. After the mosquito ingests a blood meal from an infected person, the viruses infect and replicate in the midgut, disseminate to secondary tissues and reach the salivary gland (SG), where they are ready to be transmitted to a vertebrate host. It is thought that the intrinsic discrepancies among mosquitoes could affect their ability to deal with viral infections. This study confirms that the DENV and ZIKV infection patterns of nine Ae. aegypti field populations found in geographically separate health districts of an endemic Brazilian city vary. We analyzed the infection rate, disseminated infection, vector competence, and viral load through quantitative PCR. Mosquitoes were challenged using the membrane-feeding assay technique and were tested seven and fourteen days post-infection (early and late infection phases, respectively). The infection responses varied among the Ae. aegypti populations for both flaviviruses in the two infection phases. There was no similarity between DENV and ZIKV vector competencies or viral loads. According to the results of our study, the risk of viral transmission overtime after infection either increases or remains unaltered in ZIKV infected vectors. However, the risk may increase, decrease, or remain unaltered in DENV-infected vectors depending on the mosquito population. For both flaviviruses, the viral load persisted in the body even until the late infection phase. In contrast to DENV, the ZIKV accumulated in the SG over time in all the mosquito populations. These findings are novel and may help direct the development of control strategies to fight dengue and Zika outbreaks in endemic regions, and provide a warning about the importance of understanding mosquito responses to arboviral infections.